Ethanol induces expression of the glutamate transporters EAAT1 and EAAT2 in organotypic cortical slice cultures - Zink, Mathias; Schmitt, Andrea; Vengeliene, Valentina; Henn, Fritz A.; Spanagel, Rainer (Alcoholism, 2004)
Background: Exposure of the developing brain to ethanol disposes the fetus to fetal alcohol syndrome and causes a number of changes in several neurochemical systems. In particular, the glutamatergic system is affected by ethanol. Thus, increased sensitivity of glutamate receptors and enhanced transmembrane transport of glutamate were found in primary astrocyte cultures. However, in these in vitro studies, changes in the expression of glutamate transporters were not detected. To further characterize the influence of chronic ethanol exposure on the developing brain, we assessed the transcriptional and translational regulation of glutamate transporters in a less artificial in vitro system. Methods: We exposed postnatal rat cortical organotypic slice cultures to ethanol (100 mM) for 4 and 8 days. Expression of the excitatory amino acid transporters EAAT1 and EAAT2 was analyzed in comparison to untreated controls with semiquantitative reverse transcriptase-polymerase chain reaction. In addition, changes in protein expression were detected by Western blotting. Results: In ethanol-exposed cortical slices, we observed more prominent fiber outgrowth and significantly increased gene expression (EAAT1: +35%, p= 0.029; EAAT2: +251%, p= 0.015). These findings could be verified on the protein level, because Western blot analysis revealed significantly higher levels of EAAT1 (+76%; p= 0.008) and EAAT2 (+104%; p= 0.018) in ethanol-treated slices compared with controls. Conclusions: Our results are in concert with earlier studies describing the induction of glutamate transport by ethanol. Enhanced expression of EAAT1 and EAAT2 after ethanol exposure can be viewed as a maladaptive process that disposes the developing brain to fetal alcohol syndrome.
Gesehen am 11.11.2020